Pronunciation Teaching Strategies - Siregar, Indi Hanifah Ramadani (Yayasan Daarul Huda Kruengmane, 2024)
The aim of this lesson is to provide a teacher with strategies that are suitable for use in pronunciation learning. And this is very useful for students and teachers. In Indonesia there are still many who have difficulty learning pronunciation. This happens because teachers cannot understand learning strategies, especially in the pronunciation section. In Indonesia, strategies must be implemented on how to teach easy pronunciation to provide understanding to students. Improving English pronunciation is a crucial goal for many Indonesian learners, as it directly impacts their ability to communicate effectively in a global context. This article has outlined a range of evidence-based strategies that can be employed to enhance pronunciation instruction in the Indonesian classroom. From explicit instruction on English sounds and sound patterns to the integration of pronunciation practice within communicative activities, these strategies aim to address the unique challenges faced by Indonesian learners. The use of multimodal approaches, personalized feedback, and the creation of a positive learning environment further contribute to the effectiveness of pronunciation teaching. By implementing these strategies, teachers in Indonesia can help their students develop more accurate, intelligible, and confident pronunciation skills, empowering them to engage in meaningful and successful communication in English.